THE INVOLVING BOARDING SCHOOL IN MENTAL REVOLUTION - Mawardi Lubis (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The objective of this research was to understand the involving boarding school in mental revolution. The approach be used  in research was library research with descriptive analysis method. The data  were  collected through  references review  those  connect to the involving boarding school  in mental revolution.  The research sample was 4 (four) boarding schools,  consist  of 1. PP Amanatul  Ummah Wonocolo, Surabaya,  Jawa  Timur 2. PP Suryalaya Godebag, Desa Tanjung Kerta, Pagerageung, Tasikmalaya 3. PP Nurul Barokah  Beji, Bojongsari, Purbalingga, Jawa  Tengah  4. PP Al-Anwar Sarang, Rembang, Jawa  Tengah.  The research result indicates that those  boarding schools  had  involved  in mental revolution  to educate in thousands of students and  product graduations those  had God’s marcy  mental in the word (mental rahmatan lil ‘alamin),  good character, as well as glorify divinity and humanity values